1985
DOI: 10.1177/03331024850050s222
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Flunarizine in Experimental Models Related to the Pathogenesis of Migraine

Abstract: Two new hypotheses suggest that the key pathology in migraine has a neuronal origin. A pivotal role is assigned to brain hypoxia (1) and spreading depression (SD) (neuronal depolarization spreading gradually over the cortex) (2). Flunarizine has been tested both against brain hypoxia and SD. Its potent antihypoxic properties in animal models led to its use as a prophylactic drug in migraine therapy. Earlier experiments suggested that flunarizine shortened recovery after neuronal depolarization. Recent experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

1986
1986
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 5 publications
0
25
0
1
Order By: Relevance
“…Plenty of evidences have shown that CSD is a common therapeutic target for currently prescribed migraine prophylactic drugs [29]. Preventive effects for LH prophylaxis were observed after using drugs which had been shown able to suppress CSD [30,31], yet, no effect observed for the antiepileptic drugs carbamazepine and oxcarbazepine which had been shown effective in many types of neuropathic pain. Though the non-efficiency of carbamazepine and oxcarbazepine on LH was observed only in two patients, this is consistent with their lack of efficacy on migraine [24,29] as well as on CSD [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Plenty of evidences have shown that CSD is a common therapeutic target for currently prescribed migraine prophylactic drugs [29]. Preventive effects for LH prophylaxis were observed after using drugs which had been shown able to suppress CSD [30,31], yet, no effect observed for the antiepileptic drugs carbamazepine and oxcarbazepine which had been shown effective in many types of neuropathic pain. Though the non-efficiency of carbamazepine and oxcarbazepine on LH was observed only in two patients, this is consistent with their lack of efficacy on migraine [24,29] as well as on CSD [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Nonspecific Ca 2ϩ channel antagonism previously has been shown to effect the initiation and propagation of SD in acute brain slices (Wauquier et al, 1985;Jing et al, 1993;Footitt and Newberry, 1998;Takagi et al, 1998) and in vivo (Marrannes et al, 1993). However, deciphering whether such changes are due to Ca 2ϩ channel function per se is made difficult by other nonspecific effects of the antagonists.…”
Section: P/q Ca 2؉ Channel Blockadementioning
confidence: 99%
“…Interstitial Ca 2ϩ falls by more than 90% during SD (Nicholson et al, 1977), with at least some of this loss thought to enter presynaptic terminals and thus markedly enhance Ca 2ϩ -dependent transmitter release . In fact, nonselective Ca 2ϩ channel antagonists can delay the initiation (Wauquier et al, 1985;Takagi et al, 1998) and block the propagation of SD (Jing et al, 1993). Also, generalized blockade of voltage-gated Ca 2ϩ channels can retard the induction of SD in rat neocortex (Richter et al, 2002).…”
Section: Camentioning
confidence: 99%
“…Five clinically effective migraine prophylactic drugs (valproate, topiramate, propranolol, amitriptyline, methysergide) were shown to suppress SD susceptibility [38]. Flunarizine showed a somewhat dose-dependent CSD suppression [39]. …”
Section: Discussionmentioning
confidence: 99%